Oral aspects the HIV infection in pediatric children : na actual approach - Ferreira, Dennis C.; Dias, Ana P.V.; Godefroy, Philippe; Gardioli, Daniela D.; Mello, Paula B.M.; Knupp, Rosiangela S. (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: nowadays HIV infection control have been realized in every life status, that’s to promotion for this patients the better quality oflife. Objective: to present an up-to-date focus in children infected with human immunodeficiency virus (HIV), to report several aspects of oral clini-cal manifestations. Methods:Was reviewed bibliographic material from scientific periodics, technical books, publications of international and natio-nal organizations (Medline and Lilacs – in the last ten years). Results: pediatric patients with HIV infection present individual characteristics that aredifferent from the one observed in adult patients. It begins on the privation of breast-feeding, to need a similar feeding as this entity to looking forsimulate this act, giving nutrition components and emotional care to improve on the balance development of the masticatory system, that to stay onthe normal pattern. In contrast, the experience of caries is constant mostly because of the chronic influence for the utilization of sweetened liquidmedicines, that to signalize the necessity to work of oral health promotion. Although, this medications has been promoting a decrease in the prevalen-ce of soft-tissue oral lesions. Conclusion: the Knowledge of the specific aspects of children HIV infection, allow a multidisciplinary professionalgroup to choose and to promove the best way in the promotion of health during the ambulatory clinic.